Mining of key genes for cold adaptation from Pseudomonas fragi D12 and analysis of its cold-adaptation mechanism - Bao, Changjie; Li, Muzi; Zhao, Xuhui; Shi, Jia; Liu, Yehui; Zhang, Na; Zhou, Yuqi; Ma, Jie; Chen, Guang; Zhang, Sitong; Chen, Huan (Frontiers in Microbiology, 2023)
The psychrotroph Pseudomonas fragi D12, which grew strongly under low temperatures, was screened from tundra soil collected from the permanent alpine zone on Changbai Mountain. To mine the genes critical for cold tolerance and to investigate the cold-adaptation mechanism, whole-genome sequencing, comparative genomic analysis, and transcriptome analysis were performed with P. fragi. A total of 124 potential cold adaptation genes were identified, including nineteen unique cold-adaptive genes were detected in the genome of P. fragi D12. Three unique genes associated with pili protein were significantly upregulated at different degrees of low 2 temperature, which may be the key to the strong low-temperature adaptability of P. fragi D12. Meanwhile, we were pleasantly surprised to find that Pseudomonas fragi D12 exhibited different cold-adaptation mechanisms under different temperature changes. When the temperature declined from 30°C to 15°C, the response included maintenance of the fluidity of cell membranes, increased production of extracellular polymers, elevation in the content of compatibility solutes, and reduction in the content of reactive oxygen species, thereby providing a stable metabolic environment.When the temperature decreased from 15°C to 4°C, the response mainly included increases in the expression of molecular chaperones and transcription factors, enabling the bacteria to restore normal transcription and translation. The response mechanism of P. fragi D12 to low-temperature exposure is discussed. The results provide new ideas for the cold-adaptation mechanism of cold-tolerant microorganisms.